Influence of Si nanocrystal distributed in the gate oxide on the MOS capacitance - Zhao, P. (2010)
In this paper, the authors have studied the influence of silicon nanocrystal (nc-Si) distributed in the gate oxide on the capacitance for the circumstances that the nc-Si does not form conductive percolation tunneling paths connecting the gate to the substrate. The nc-Si is synthesized by Si-ion implantation. The effective dielectric constant of the gate oxide in the nc-Si distributed region is calculated based on a sublayer model of the nc-Si distribution and the Maxwell-Garnett effective medium approximation. After the depth distribution of the effective dielectric constant is obtained, the MOS capacitance is determined. Two different nc-Si distributions, i.e., partial and full nc-Si distributions in the gate oxide, have been considered. The MOS capacitance obtained from the modeling has been compared to the capacitance measurement for a number of samples with various gate-oxide thicknesses, implantation energies and dosages, and an excellent agreement has been achieved for all the samples. A detailed picture of the influence of implantation energy and implantation dosage on the MOS capacitance has been obtained.